FUNCTIONAL TRAPS OF THE FULL ARCH IMPLANT SUPERSTRUCTURES IN IMPLANTOLOGY - Bratu Emanuel Adrian; Borsanu Ioan; Rusu Laura-Cristina; Sinescu Cosmin; Antonie Sergiu (Romanian Society of Oral Rehabilitation, 2023)
Aim of the study is to analyse the mechanical problems of implant restorations: the precise passive fit, the fracture resistance-aging, the micro fractures, the change in colour and the design of both infrastructure and superstructure. Material and methods We evaluate the same full arch restoration with the five most used material combinations and a mechanical failure test and numeric design simulations of forces at bone level. Results: Generally, two extensions failed faster than the single extension. Conclusions The patients' expectations on the success of the implant and the predictability are high compared to their reluctance towards treatment costs and duration; it is particularly important to clarify this aspect from the beginning of the treatment.